Alcoxotechnology for obtaining heat-resistant materials based on rhenium and ruthenium - E. S. Kulikova; O. V. Chernyshova; L. A. Nosikova; R. D. Svetogorov; D. V. Drobot; I. A. Mikheev (Тонкие химические технологии)
Objectives. To develop physical and chemical bases and methods to obtain rhenium–ruthenium isoproxide Re4-yRuyO6(OPri)10 —a precursor for obtaining a high-temperature alloy—from ruthenium acetylacetonate and rhenium isoproxide acquired by electrochemical methods.Methods. IR spectroscopy (EQUINOX 55 Bruker, Germany), X-ray phase and elemental analyses, energy-dispersive microanalysis (EDMA, SEM JSM5910-LV, analytical system AZTEC), powder X-ray diffraction (diffractometer D8 Advance Bruker, Germany), experimental station XSA beamline at the Kurchatov Synchrotron Radiation Source.Results. The isoproxide complex of rhenium–ruthenium Re4-yRuyO6(OPri)10 was obtained, and its composition and structure were established. Previously conducted quantum chemical calculations on the possibility of replacing rhenium atoms with ruthenium atoms in the isopropylate complex were experimentally proven, and the influence of the electroconductive additive on the composition of the obtained alloy was revealed.Conclusions. Physical and chemical bases and methods for obtaining rhenium–ruthenium isoproxide Re4-yRuyO6(OPri)10 were developed. The possibility of using rhenium–ruthenium Re4-yRuyO6(OPri)10 as a precursor in the production of ultra- and nanodisperse rhenium–ruthenium alloy powders at a record low temperature of 650°C were shown.